2012
DOI: 10.5539/jedp.v2n2p110
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Self-efficacy and Achievement Goals: A Developmental Approach

Abstract: An emerging interest in cognition and motivation has recently involved the study of rate of change of self-efficacy and achievement goals. We used latent growth modeling (LGM) to test a structural equation model that involved prior academic grades, self-efficacy, mastery and performance-approach goals, and academic achievement measured over a two-year period. A sample of 228 (106 females, 122 males) of second-year students enrolled in mathematic participated in this study. Multivariate growth curve analyses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 90 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…"You"re really good at mathematics" or "This is a doable task, just be attentive and thoughtful") and the usage of authentic assessment tasks in units is more likely to emphasize a mastery goal orientation. Consequently, this influence promotes individual growth and mastery of mathematical skills (Phan, 2012 Motivation theorists always ask in order to understand how motivation affects choice, persistence, and effort. Some of them argue that individuals" activity choice, persistence, and effort can be explained by their judgments about their ability(efficacy-expectations) how well they will complete the activity (outcome-expectations) and the extent to which they value the activity(task-value) (Wigfield, 1994).…”
Section: Contributions Of Social-cognitive Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…"You"re really good at mathematics" or "This is a doable task, just be attentive and thoughtful") and the usage of authentic assessment tasks in units is more likely to emphasize a mastery goal orientation. Consequently, this influence promotes individual growth and mastery of mathematical skills (Phan, 2012 Motivation theorists always ask in order to understand how motivation affects choice, persistence, and effort. Some of them argue that individuals" activity choice, persistence, and effort can be explained by their judgments about their ability(efficacy-expectations) how well they will complete the activity (outcome-expectations) and the extent to which they value the activity(task-value) (Wigfield, 1994).…”
Section: Contributions Of Social-cognitive Theorymentioning
confidence: 99%
“…Elliot & Harackiewicz, 1996) describe goal orientation as students" reasons for engagement in an activity for learning. However, it is important for educators to consider the fact that learning experiences may influence students" beliefs about learning, and this influence may result in the adoption of different goal orientation (Phan, 2012). In terms of expectancyvalue theory, an effective way to motivate learners is to increase their expectancies by consciously organizing the conditions in which they will have more positive beliefs about their ability or competence.…”
Section: Contributions Of Social-cognitive Theorymentioning
confidence: 99%
“…Past research (e.g., Bandura, 1986;Credé & Phillips, 2011;Phan, 2012) has shown that various motivational constructs in MSLQ, such as self-efficacy, correlate with AGO constructs (e.g., Phan, 2012), such as mastery goal orientation. These findings guide our second research question: can we predict students' achievement goal orientation from their self-reported learning strategies?…”
Section: Introductionmentioning
confidence: 99%
“…Developmental trajectories or pathways have been gaining increasing attention as a way of conceptualizing development over time (e.g., Phan, 2012). However, the roles parents play on those trajectories has gone largely unexamined.…”
Section: Introductionmentioning
confidence: 99%